Cutting too close to the bone? Fragilizing the democratic resilience of public administration - Catalin Raiu (International Review of Administrative Sciences, 2026)
This paper develops a conceptual perspective on how a series of major crises, from the “war on terror” (2001) to today's wave of budgetary austerity measures, has created a widespread sense of perpetual emergency among political leaders. Through a habituation effect, prolonged exposure to crisis-driven exceptional measures has gradually normalized illiberal and populist practices, even among mainstream liberal-democratic governments. The paper addresses a notable gap in the existing literature. While democratic backsliding and bureaucratic politicization have received considerable scholarly attention, the long-term cumulative impact of stratified crises on the democratic resilience of public administration remains underexplored. By conceptualizing the habituation effect as a central mechanism, this study identifies four governance trends that undermine the neutrality, autonomy, and democratic character of public administration: the (re)politicization and bullying of civil servants, the erosion of autonomous public agencies, the rapid and often poorly regulated deployment of digital technologies and artificial intelligence, and the increasing bypassing of parliamentary oversight. Ultimately, the study argues that public administration should not be “cut too close to the bone” and therefore instrumentalized to achieve short-term efficiency. Instead, it should be empowered to adopt a public-value-oriented approach that safeguards its democratic resilience and serves as a critical institutional veto point against populist and illiberal encroachments. Points for practitioners Efforts to reduce the size of public administration must never weaken its internal checks and balances or its ability to resist populist pressures and illiberal political interference. Simplifying rules and procedures should always be paired with a stronger focus on the core mission of modern public administration—delivering real value to citizens and society. When using artificial intelligence in the public sector, actively engage AI specialists and relevant stakeholders to prevent problems such as data biases, discrimination, and unfair outcomes. Greater emphasis should be placed on protecting and empowering independent agencies, as they play a vital role in safeguarding the democratic resilience of public administration.